Digital Twin concept and architecture for fleets of hydrogen electrolysers - Alsharif, Sharaf; Huxoll, Nils; Wibbeke, Jelke; Grimm, Tobias; Brand, Michael; Lehnhoff, Sebastian (Frontiers in Energy Efficiency, 2024)
The expected increase in green hydrogen demand in the near future necessitates scalingup the hydrogen production plants with the goal of reducing the hydrogen production costs.Nevertheless, a quick scale-up limits the time to test new designs, optimize operation schedules and build up knowledge for production parameters. The Digital Twin concept applied on a fleet of electrolysers is proposed as a digitization tool to contribute to this scale-up process by providing a comprehensive view of the entire electrolysers fleet as well as constructing the feedback connection to the electrolysers manufacturing process. Such Fleet Digital Twin approach can improve the efficiency and scalability of green hydrogen production using water electrolysis. This paper presents a concept of a Fleet Digital Twin and discusses its architecture requirements and design. By applying the Digital Twin concept at different levels of the system, fleet knowledge services are enabled by leveraging the availability of fleet-wide data. The proposed architecture design provides a solid foundation for future development and implementation of Fleet Digital Twins in industrial applications.